Stemmer's (Kaposi-Stemmer-) sign – 30 years later - Brenner, E.; Putz, D.; Moriggl, B. (Phlebologie, 2007)
Background: Since the first description 30 years ago the Kaposi-Stemmer-sign is used consistently in the diagnostics of lymphoedema. Since then the original definition was extended or changed several times by other authors. Additionally, the underlying morphology of this clinical sign was not investigated. Material, methods: The second toes of both a patient with lymphoedema (stage III; iL5VxF5) and a healthy subject were compared sonographically, macroscopically and microscopically. Results: In lymphoedema both cutis and subcutis of the second toe were thickened, the structure of the dermal layers destroyed. An accumulation of oedematous fluid in free spaces within the subcutaneous tissue as well as lymphatic vessels could not be found. Discussion: The different definitions and graduations of the Kaposi-Stemmer-sign make the diagnosis of lymphoedema more difficult and concomitantly the clinical and scientific comparability. Morphologically, an accumulation of oedematous fluid could not be proven due to weak or missing streaks of fibrous tissue within the subcutis of the toe.
Keywords: Stemmer sign; Kaposi-Stemmer-sign; lymphoedema